Emissions Reduction of a Chemical Process Plant by Maximizing Energy Recovery, Minimizing Energy Losses and Fuel Switching - Gabr, Eman M; Mohamed, Soad M (Review of Energy Technologies and Policy Research, 2019)
Increasing population and technology progress required more energy consumption and more fuel combustion. The major source of pollution is harmful gasses emission due to fossil fuel combustion. In this work, we chose a chemical process as a case study for gasses emission reduction through the application of energy management methodology including four techniques. Firstly, maximizing of energy recovery realized by designing a heat exchangers network (HEN) where the rate of energy saving and so on emission reduction reached to 60% compared to the existing case. Secondly, minimizing of heat losses by using optimum pipes insulation where reduction of fuel consumption reached to 15%-20% and it is directly reduced gasses emission by the same percentage. Thirdly, fuel switching from fuel oil to natural gas reduced gasses emission by 44% compared to the existing case. The fourth one, integration between the last three techniques can guarantee a reduction of harmful gasses emission by 80% compared to existing unit conditions.